Performance Analysis Cooling Tower Type Induced Draft with PVC Plate Filling Material - Mochamad Rizky Pradana; Astrie Kusuma Dewi; Natasya Aisah Septiani; Asepta Surya Wardhana; Muhammad Ramdhan; Wendy Triadji Nugroho (Politeknik Negeri Lhokseumawe, 2023)
In the industry, savings in water use are needed, so that the output water from the condenser will be recirculated for reuse so that it does not need new water. The output of the condenser, which is hot water with a temperature of 45 °C, needs to be conditioned to a normal temperature. So they designed a cooling tower to reduce the temperature of the hot water through direct contact with the air. Filling material is a component that is very influential on the performance of the cooling tower because, in this material, there is direct contact between hot water and dry water in opposite directions. The purpose of this study was to determine the height of the PVC plate filling material that has adequate effectiveness so that the hot water in the cooling process runs optimally. In this study, several tests were carried out that showed the performance of the cooling tower, including range, approach, cooling effectiveness, cooling capacity, and the rate of evaporation of water into the air. So from this research, it was found that the optimal height of fill material is 20 cm, which has the highest relative humidity (RH) of the outgoing air, which is 87.2%, and the lowest exit air temperature of 29.3°C